A Comparative Study of Iraqi Patients with Bedsore and other Inpatients as a Control Group - AlKareem, Diyar A.; Al aubydi, Mouruj A. (Iraqi Journal of Science, 2022)
Bedsore (pressure ulcers)is a major nurse-careoutcome. There are many influences that can contribute to the progress of pressure ulcers, but the final common pathway to ulceration is tissue ischemia. This study aimed to detect some etiological factors that predispose to bedsore. The study was conducted on patients attending intensive care departments. Out of 82 inpatients who suffered from pressure ulcer, 54were males and 28were females. Specimens were collected during the period of September, 2019 –February, 2020 from different Hospitals (Alkadhimiya Teaching Hospital, General Hospital of AlshaheedAl-Sadr, and Medical City/ Ghazi Al-Hariri hospital) in Baghdad, Iraq. Simultaneously, other 20 specimens were collected as control frominpatientswho did not suffer from any skin lesion.The patients were categorizing according to the causative agent into 48 patients with chronic diseases (58.6%), 26 with accidental and surgical processes (31.7%), and 8 dehydrated cases (severe diarrhea) (9.7%). The demographic results showed that malesconstituted a percentage of 65.9% of patients, while 34.1% were females. The majority of the patients wereat an age range of 36-65 years. The study also revealed that smoking did not affect significantly bed sore development. In addition, most patients were under chronic disease, and diabetes mellitus incidence significantly varied among different age groups. The results of the microbiological study showed that the most prevalent microbial isolates followed the order Staphylococcus spp.>Enterobacteriaceae spp. > Fungi >Acinetobacter spp. > Bacillus spp. > Pseudomonas spp. and Streptococcus spp. >Corynobacterium. The resultsrevealed no significant differences in microbial distribution between patients and control group.